2018
DOI: 10.1159/000487392
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Diet and Drug Use Preceding Alcoholic Hepatitis

Abstract: Background: Alcoholic hepatitis (AH) is a severe manifestation of alcohol-related liver disease characterised by jaundice and liver failure. It is not known what might trigger an episode of AH. We interviewed patients to investigate changes in behaviour before the onset of AH. Methods: Structured interviews were performed with patients with AH to examine their alcohol use, diet, drug use and smoking habit. Clinical and laboratory results were noted. Patients were followed up for 12 months after interview. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…These negative consequences subsequently lead to behavioural, emotional, social, and academic problems in later life [21]. Researchers have shown that harmful alcohol consumption leads to the development of cardiovascular diseases [18], cancer [22], liver diseases [23], hepatitis [24], risky sexual behaviours and sexually transmitted diseases [25,26], mental and behavioural disorders, injuries, violence [2], and poor academic performance [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…These negative consequences subsequently lead to behavioural, emotional, social, and academic problems in later life [21]. Researchers have shown that harmful alcohol consumption leads to the development of cardiovascular diseases [18], cancer [22], liver diseases [23], hepatitis [24], risky sexual behaviours and sexually transmitted diseases [25,26], mental and behavioural disorders, injuries, violence [2], and poor academic performance [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…One of the key contributors to the development of protein-calorie malnutrition is accelerated catabolism, primarily induced by patients who reduce their energy intake from food while relying on the caloric value of alcohol to meet their basal metabolic expenditure, thereby limiting the contribution of essential macronutrients and micronutrients[ 100 ].…”
Section: Alcohol-related Liver Diseasementioning
confidence: 99%
“…Alcohol consumption has a synergistic effect with viral hepatitis in the progression of liver disease (Tikhanovich et al, 2014;Dolganiuc, 2015). In addition, alcohol is a well-known causal factor for non-infectious liver diseases, including hepatitis (Parker & Neuberger, 2018) and liver cirrhosis, and the latter is associated with high mortality (Sandahl et al, 2010) (section 1.2.3.3).…”
Section: Viral Hepatitismentioning
confidence: 99%